Non diligas meretricem et dimittas sponsam tuam - Imbach, Ruedi (Revue des sciences philosophiques et théologiques, 2013)
The present article offers an analysis of Bonaventure’s lectures on the Six Days of Creation delivered in Paris in 1273. The twenty-three talks not only lay out a precise understanding of philosophy, its object and its limits, but the Franciscan also vigorously argues in these sermons against the idea of an autonomous philosophy that is not determined by theology. The examined work bears interesting testimony to the intellectual debates of the 1270’s and helps to better understand the impact of Aristotle’s introduction in the West. At the same time, bonaventurian preaching implies an interesting alternative appreciation of metaphysics, an approach to primary philosophy that cannot be reduced to an onto-theological paradigm.